P10: Is the OctreoScan score a predictive factor of response to somatostatin analogs treatment? - Damiano, Vincenzo (J Thorac Dis, 2015)
BACKGROUND: The somatostatin receptor expression in thymic neoplasms is assessed in vivo imaging by (111)In-octreotide SPECT (OctreoScan). This retrospective study aimed to verify the predictive role of intensity expression of OctreoScan to somatostatin analogues treatment. METHODS: We evaluated 28 patients (14 male and 14 female with a median age of 54 years, range, 27–78 years) with thymic tumors candidated to somatostatine analogs therapy as second or third line of treatment or maintenance treatment. For this reason all of them performed OctreoScan of the thorax and tumor-to-background ratio was determined on the 24-h coronal sections. Thymic tumors were classified by WHO 2004 and staged according to Masaoka-Koga system. Specifically, AB three patients; B1 two patients; B2 five patients; B3 nine patients; B2/B3 three patients; thymic carcinoma five patients; B3/thymic carcinoma one patient. All the patients had a III of IV stage of disease. Lesions with pathologically increased tracer uptake were categorized according to the following 3-pointscore: equivocal, probably pathologic, and definitely pathologic. RESULTS: All patients were OctreoScan positive, four with an equivocal point score, nineteen and five with a probably and definitely pathological score respectively. Somatostatin analogs were administrated as second or third line of therapy in 10 patients, as maintenance therapy in 16 patients and as both of modality in two patients. Median time to progression was 16 months (range, 6–77 months) and it was not influenced by uptake pathological score. CONCLUSIONS: The intensity of uptake of Indium-111-DTPA-D-Phe1-octreotide in thymic tumors is not a predictive factor of response to somatostatin analogues treatment. The OctreoScan positivity is the best rationale for treating thymic epithelial tumors (TETs) with somatostatin analogs.